EDUCATION AND RESEARCH DUALITY - THE DETERMINING CHARACTERISTIC OF HIGHER EDUCATION - Volodymyr Lugovyi; Olena Orzhel; Olena Slyusarenko; Zhanna Talanova (National Academy of Educational Sciences of Ukraine, 2018)
The article, based on new empirical data, semantic analysis and systematic interpretation of the concepts of "education", "science", "research and development" (R&D), deepens and expands the understanding of higher education as a dichotomy of education and research. The subordinated character of such dichotomy is demonstrated, when the main (primary) role belongs to education and supplementary (secondary), although essential, to R&D. It is argued that the first two subordinately related keywords in the mission statements of higher education institutions - "education" and "research" - serve as canonical birthmark and a criterion for identifying these institutions. The immanent dichotomy of higher education can be implemented in two ways: 1) as the dual "teaching and research" function of the academic staff (the main mode) and 2) via organization of R&D as a separate HEI activity, additionally to the main mode. According to the ratio of educational and research activities, HEIs can be divided into two types: academic (research) and professional (applied). By calculating the magnitude of correlations, it is proved that organization of national higher education and research areas depends on the size of the country and its resources, which overrules the incorrect comparison of Ukraine with small countries. The juxtaposition of universities and research institutions (academies) in Ukraine in order to diminish the role of the latter, following the example of small countries, instigates the disorganisation of domestic higher education and research areas and contradicts the laws and trends of world development.